Evidence from Cochrane systematic reviews for the dissemination control of the COVID-19 infection (SciELO Preprints, 2020)
Introduction: The COVID-19 infection has high transmissibility and several measures have been adopted for dissemination control. Objective: To identify and summarize the evidence from the Cochrane systematic reviews (SR) on measures to control the dissemination of the COVID-19 infection. Study design: This review of Cochrane SR has carried out in the Division of Vascular and Endovascular Surgery and in the Division of Emergency Medicine and Evidence-Based Medicine of the Universidade Federal de São Paulo, Brazil. Methods: A comprehensive search in the Cochrane Database of Systematic Reviews retrieved all Cochrane SR directly related to control measures for the COVID-19 dissemination. The main characteristics and results of all included SR were summarized and discussed. Results: Three Cochrane SRs were included in the qualitative synthesis and they evaluated populational and individual measures to control the dissemination of COVID-19. Conclusion: Low-certainty evidence show that quarantine of people exposed to those confirmed or suspected COVID-19 cases prevented 44% - 81% of incident cases and 31% - 63% of deaths compared to no measures and as sooner the quarantine measures are implemented, greater costs are saved. High-confidence evidence showed that clear communication about infection control and prevention guidelines was vital to its implementation. Low-certainty evidence showed that people with a long gown had less contamination than those with a coverall, and the coverall was more difficult to doff. Other SRs are desirable for controlling the dissemination of the COVID-19 infection.